A novel beer fining agent extracted from hops - Gadon, A.G. (2020)
On a shelf or in a bar, beers are intended to be served clear, bright and free from visible haze. Industrialization and novel brewing technologies have pushed brewers to develop beers that have the required shelf-life in terms of product quality, flavour, and appearance. During beer brewing, clarification post-fermentation is an important step to remove the majority of haze material prior to further steps such as filtration and bottling. Fining agents are used to accelerate sedimentation of yeast and haze particles within beer, in order to reduce the time required for this haze material to settle. The focus of this study was towards the development of a novel fining agent extracted from spent hops. Spent hops contain significant amounts of polyphenols. Because of the high affinity of some phenolics with haze active proteins, they represent a good candidate for the flocculation of beer haze particles. As it is also sourced from hops, this product has great potential to replace other animal-based products such as isinglass finings. The extraction procedure was firstly assessed in order to define the optimal protocol to extract the active component from the plant material. Extraction using 70% acetone(aq.) yielded the highest amount of proanthocyanidin polyphenols and also produced the best performance in beer fining. Then, the application of this extract to a broad variety of beers from laboratory to brewery scale was investigated. The hop extract has been found to effectively fine beers produced with a range of yeast strains and was able to remove efficiently haze from ales and lager beers when introduced at the individually determined optimal dose range. Beneficial impacts in fining performance were observed when using the hop extract in combination with silicate auxiliary finings. An opposite effect was found when using the novel finings with stout beers, as haze was created during the fining reaction. Post-fining laboratory filtration trials using cellulose filters showed that the hop extract, when combined with auxiliary finings, improved the filterability of finished beer relative to isinglass fined beer. The characterisation of the active material was then conducted, with a particular focus on the molecular weight and size range. Earlier research by Linforth and colleagues demonstrated the presence of polyphenolic material, more specifically proanthocyanidins. These compounds can be present as small monomers and dimers or as long polymeric assemblies of catechin and epicatechin. The lack of reference standards and the complexity of the molecular distribution present analytical challenges to define the structure and the molecular weight of these compounds. A novel method was developed using Analytical Ultracentrifugation to identify the molecular weight distribution of hop proanthocyanidins in the active fining fractions. Sedimentation velocity experiments revealed a heterogeneous fraction with discontinuous peaks. Sedimentation equilibrium experiments allowed the assignments of molecular weights, with compounds found in the hop extracts, up to 100 kDa. Major differences were observed comparing hop extracts from different varieties in both proanthocyanidin content and beer fining efficiency. The presence of high molecular weight polymers was shown to strongly correlate with superior fining activity (assessed in terms of beer haze removal and sediment formation). Impacts of the hop finings addition on finished beer parameters were also investigated. No major differences were identified using hop extract finings compared to other fining strategies when observing the beer volatile profile through gas chromatography after an accelerated ageing study. Significant reduction (p < 0.05) in iron concentrations was found when using the hop extract in lager beers compared to isinglass treated beer and an unfined control. Improved oxidative stability was assessed by electron spin resonance spectroscopy for lager beers treated with the hop extract. Introducing this fining agent during the brewing process may thus also benefit the brewer for desirable aspects such as shelf-life and quality.